Do You Have to Win It to Fix It? A Longitudinal Study of Lottery Winners and Their Health Care Demand - Terence Chai Cheng; Joan Costa-i-Font; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2015)
We exploit lottery wins to investigate the effects of exogenous changes to individuals' income on health care demand in the United Kingdom. This strategy allows us to estimate lottery income elasticities for a range of health care services that are publicly and privately provided. The results indicate that lottery winners with larger wins are more likely to choose private health services than public health services from the National Health Service. For high-income individuals without private medical insurance, the larger their winnings, the more likely they are to obtain private overnight hospital care. For privately insured individuals, the larger their winnings, the more likely they are to obtain private care for dental services and for eye, blood pressure, and cervical examinations. We find that medium to large winners (≥ 500) are more likely to have private health insurance. Larger winners are also more likely to drop coverage earlier, possibly after their winnings have been exhausted. The elasticities with respect to lottery wins are comparable in magnitude to the elasticities of household income from fixed-effect models.
Keywords: H42; I11; D1; 330; lottery wins; health care; income elasticity; public-private